Madecassic Acid Ameliorates the Progression of Osteoarthritis: An in vitro and in vivo Study - Fu X; He S; Wang L; Xue Y; Qiao S; An J; Xia T (Dove Medical Press, 2022)
Xuejie Fu,1,* Shuangjian He,2,* Liang Wang,2 Yangyang Xue,2 Shigang Qiao,1 Jianzhong An,1 Tingting Xia1 1Institute of Clinical Medicine Research, Suzhou Science & Technology Town Hospital, Suzhou, JiangSu, People's Republic of China; 2Department of Orthopedics, Suzhou Science & Technology Town Hospital, Suzhou, JiangSu, People's Republic of China*These authors contributed equally to this workCorrespondence: Tingting Xia, Institute of Clinical Medicine Research, Suzhou Science & Technology Town Hospital, Suzhou, 215153, JiangSu, People's Republic of China, Tel +86 18523986726, Email xtt_92@126.comPurpose: Osteoarthritis (OA) places a significant burden on society and finance, and there is presently no effective treatment besides late replacement surgery and symptomatic relief. The therapy of OA requires additional research. Madecassic acid (MA) is the first native triterpenoid compound extracted from Centella asiatica, which has a variety of anti-inflammatory effects. However, the role of MA in OA therapy has not been reported. This study aimed to explore whether MA could suppress the inflammatory response, preserve and restore chondrocyte functions, and ameliorate the progression of OA in vitro and in vivo.Methods: Rat primary chondrocytes were treated with IL-1β to simulate inflammatory environmental conditions and OA in vitro. We examined the effects of MA at concentrations ranging from 0 to 200 μM on the viability of rat chondrocytes and selected 10 μM for further study. Using qRT-PCR, immunofluorescent, immunocytochemistry, and Western blotting techniques, we identified the potential molecular mechanisms and signaling pathways that are responsible for these effects. We established an OA rat model by anterior cruciate ligament transection (ACLT). The animals were then periodically injected with MA into the knee articular cavity.Results: We found that MA could down-regulate the IL-1β-induced up-regulation of COX-2, iNOS and IL-6 and restore the cytoskeletal integrity of chondrocytes treated with IL-1β. Moreover, MA protects chondrocytes from IL-1β-induced ECM degradation by upregulating ECM synthesis related protein expression, including collagen-II and ACAN, and further down-regulating ECM catabolic related protein expression, including MMP-3 and MMP-13. Furthermore, we found that NF-κB/IκBα and PI3K/AKT signaling pathways were involved in the regulatory effects of MA on the inflammation inhibition and promotion of ECM anabolism on IL-1β-induced chondrocytes.Conclusion: These findings suggest that MA appears to be a potentially small molecular drug for rat OA.Keywords: osteoarthritis, madecassic acid, inflammatory responses, cartilage degradation